Autoethnographic Notes on the Experience of Creating Playgrounds from Leftover Materials in the Process of Initial Preschool Teacher Education - Lazarević, Milijana B. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2024)
Play represents a natural expression of a child’s relationship with the world and, as such, forms the basis for the manifestation of all dimensions of children’s well-being. However, global trends in scholarisation and the commercialization of play often lead to a reduction in opportunities for open play, particularly for play that is not saturated with materials that have predetermined meanings and purposes. This paper emerged from the research process on the significance of loose parts as play materials among teachers and second-year students in the „Preschool Teacher“ program at the College of Applied Studies for Preschool Teachers and Business Informatics "Sirmium" in Sremska Mitrovica. The aim of the research is to explore, through autoethnographic notes, the experience of researching and creating loose parts playground within the educational process. The findings suggest that the experience of investigating the significance of unstructured play materials and creating loose parts playground in support of open play leads to insights about the implicit pedagogies of teachers and students regarding the child, play, and how it can be supported in the community. Thus, such research has a transformative character concerning approaches in the education of future preschool teachers.